A review of past and projected changes in Australia's rainfall. (7th March 2019) - Dey, Raktima; Lewis, Sophie C.; Arblaster, Julie M.; Abram, Nerilie J.
Abstract : There has been much attention given to the spatial and temporal characteristics of changes in mean and extreme rainfall over Australia during the past century. As Australia is the second driest continent on Earth, reliable projections around the trends and variability in future rainfall are crucial for policymakers and water resource management. This article comprehensively reviews the current published literature on trends in Australia's rainfall from pre‐instrumental and instrumental records, the climatic drivers of Australia's rainfall variability, attribution of the long‐term trends, extreme rainfall attribution methods with particular reference to a recent case study (2010–2012 east Australia rainfall event) and projected changes of mean and extreme rainfall over Australia during the 21st century. Notable trends in the observational record of rainfall in Australia are a decrease in mean rainfall in southwest and southeast Australia and an increase in northwest Australia since 1950. The general consensus of research into Australia's future rainfall is that mean rainfall will continue to decrease in southwest Australia in a warming world, while changes over northern and eastern Australia remain uncertain. There are still significant knowledge gaps around the causes of observed trends in rainfall both in the mean and extremes, the ability of climate models to accurately represent rainfall in the Australian region and future rainfall projections. These gaps are identified, and avenues for future research directions are proposed. This article is categorized under: Paleoclimates and Current Trends > Modern Climate Change Abstract : Outline of the regions that experience major rainfall trends in Australia. Northwest Australia (NWA; 10°–25°S, 110°–135°E), southeast Queensland (SEQ; 22°–30.5°S, east of 150.5°E), southwest of Western Australia (SWWA; southwest of the line joining 30°S, 115°E, and 35°S, 120°E), southeast Australia (SEA; 33°–44°S, 135°–154°E). The current article reviews the recent scientific literature on rainfall in the pre‐instrumental and instrumental period over Australia, including the underlying mechanisms (e.g., impact of anthropogenic changes, and natural variability) of the regional and seasonal variations and future projections. We discuss progress in detection and attribution and the future avenues in this field.